Differentials and determinants of neonatal mortality in Pakistan: A cross sectional analysis (PDHS 2017-18) - Asifa Kamal; Abeera Shakeel (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: To investigate differentials and determinants of neonatal mortality in Pakistan. Methods: Study design was cross sectional. Data from Pakistan Demographic and Health Survey (PDHS 2017-18) was used. Data collection period for PDHS 2017-18 was from 22 November 2017 to 30 April 2018. Neonatal mortality rates (NMRs) were computed to observe the differentials in NMR for various categories of socio-demographic factors. Cox proportional hazard model was fitted to identify significant factors affecting neonatal mortality. Results: Hazard of neonatal mortality had significantly decreased as household size increased (HR 0.41 and HR 0.36). Household with improved toilet facility had significantly lower chances (HR 0.57) of neonatal death as compared to that with unimproved toilet facility. Significantly elevated risk (HR 5.56) of neonate death was observed in case of multiple births. Children had better chances (HR 0.32; HR 0.34) of surviving in neonatal period as duration of birth spacing increased (24-35 months; 36 or more months). Conclusion: Household size, improved toilet facilities, multiple births and preceding birth intervals were found to have significant effect on neonatal mortality. Significant protective factors of neonate deaths were large household size, improved toilet facilities, singleton births and long birth interval. Keywords: PDHS 2017-18, Neonatal Mortality Rate, Cox Proportional Hazard Model